2011
DOI: 10.1016/j.biopsych.2011.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior Is Associated with Reduced Corpus Callosum Area

Abstract: Background: Corpus callosum (CC) size has been associated with cognitive and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 54 publications
(41 reference statements)
4
37
1
2
Order By: Relevance
“…Interestingly, we found no correlations between number of attempts in lifetime and significant volumetric findings. Additionally, unlike some other studies of suicidality, which selected for participants aged 65 and older (Cyprien et al, 2011;Hwang et al, 2010), this study removed the confound of old age (mean age of 30.9 years), avoiding possible problems associated with the increased risk of brain atrophy in aging.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, we found no correlations between number of attempts in lifetime and significant volumetric findings. Additionally, unlike some other studies of suicidality, which selected for participants aged 65 and older (Cyprien et al, 2011;Hwang et al, 2010), this study removed the confound of old age (mean age of 30.9 years), avoiding possible problems associated with the increased risk of brain atrophy in aging.…”
Section: Discussionmentioning
confidence: 95%
“…Research has also shown parietooccipital volume reductions in suicidal patients with bipolar disorder (Benedetti et al, 2011), borderline personality (Soloff et al, 2012), and various psychotic disorders (Giakoumatos et al, 2013). Several studies have noted volumetric differences in the insula (Giakoumatos et al, 2013;Soloff et al, 2012), thalamus (Giakoumatos et al, 2013), basal ganglia (Benedetti et al, 2011;Dombrovski et al, 2010;Vang et al, 2010;Wagner et al, 2011), posterior corpus callosum (CC; (Cyprien et al, 2011), hippocampus (Colle et al, 2015) and amygdala (Monkul et al, 2007;Spoletini et al, 2011;Wagner et al, 2011). These areas have broad connections to the fronto-limbic system and temporal lobe; therefore, these regions could contribute to the emotion dysregulation associated with suicidal behavior.…”
Section: Introductionmentioning
confidence: 92%
“…The first study found a reduced area in the posterior third of the CC in elderly suicidal patients when compared to elderly patients with current or lifetime major depressive disorder or anxiety disorder and healthy controls (Cyprien et al, 2011). Another important report from Matsuo and colleagues showed that suicidal patients with BD were more impulsive than the comparison groups and that suicidal BD patients showed a significant inverse partial correlation between the Barratt Impulsiveness Scale (BIS-11) total score and the anterior genu area.…”
Section: Introductionmentioning
confidence: 97%
“…Les noyaux gris centraux seraient également atteints, en particulier le putamen dont le volume était diminué chez des suicidants par rapport à des témoins affectifs (Dombrovski et al, 2011a). La connectivité inter-hémisphé-rique serait de moins bonne qualité chez les suicidants âgés avec des altérations du tiers postérieur du corps calleux (Cyprien et al, 2011).…”
Section: Neuroimagerieunclassified